A copolymer containing quinine structure and its preparation method and application

By designing copolymers containing quinine structures, the problems of poor alkali resistance and low hydroxide ion conductivity in alkali anion exchange membrane fuel cells are solved, efficient ion conduction and good mechanical properties are achieved, and the overall performance of the membrane material is improved.

CN119161564BActive Publication Date: 2025-03-18YANTAI GEM CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411666702.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The anion exchange membrane of existing alkaline anion exchange membrane fuel cells has problems such as poor alkali resistance and stability, low hydroxide ion conductivity and severe water absorption and swelling, which limits its development.

Method used

A copolymer containing quinine structure was designed to construct efficient ion conduction channels through the structural characteristics of polymer functional groups (such as imidazole and quinine) and the "ether-free" design of the backbone, thereby enhancing the alkali resistance and mechanical properties of the membrane material.

Benefits of technology

It achieves high ion conductivity, good alkali resistance and mechanical properties, reduces water absorption and swelling rate, improves the overall performance of membrane materials, and has great potential for anionic membranes of alkaline fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161564B_ABST
    Figure CN119161564B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of membrane materials, and in particular to a copolymer containing a quinine structure and a preparation method and application thereof. The copolymer containing a quinine structure comprises the structure: #imgabs0#; Y 1 ~Y 5 are each independently selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent, Ar 1 ~Ar 5 is independently selected from substituted or unsubstituted arylene, aralkylene, heteroalkylene, alkylene, perfluoroalkylene, heteroarylene or absent, Ar 6 ,Ar 7 R is independently selected from substituted or unsubstituted aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl, heteroaryl or hydrogen; 1 ~R 10 Each is independently selected from hydrogen, alkyl, aryl, aralkyl, heteroalkyl, heteroaryl and perfluoroalkyl. The ion exchange membrane material prepared from the copolymer has excellent alkali stability and good conductivity, and the preparation method is simple and easy, and has great application potential in anion membranes of alkaline fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copolymer containing a quinine structure and a preparation method and application thereof, belonging to the technical field of membrane materials. Background Art

[0002] Fuel cells are a clean and efficient energy conversion technology. In recent decades, with the application and development of key materials such as perfluorosulfonic acid proton exchange membrane (Nafion) and palladium-carbon catalysts, the research on proton membrane fuel cells has achieved milestone development. Various commercial fuel cell vehicles powered by them have been reported one after another, and their performance can compete with internal combustion engine vehicles. However, due to its strong acidic operating environment, the operation of proton membrane fuel cells must rely on expensive catalysts such as palladium and Nafion membrane materials, which restricts its further commercialization. Therefore, in recent years, researchers have turned their attention to alkaline anion exchange membrane fuel cells. Its potential advantages are becoming increasingly obvious: fuel and oxidant have higher reaction kinetics under alkaline conditions, which can not only reduce the loading of precious metal catalysts, but also use non-precious metal catalysts; polymer anion exchange membrane as electrolyte can avoid the precipitation of carbonates and their deposition on the electrode surface; the movement direction of ions in the electrolyte in alkaline anion exchange membrane fuel cells is opposite to that of the fuel, which can well hinder the penetration of fuel, alleviate the fuel penetration problem, and simplify the water management of the battery. However, the research in this field is not mature enough. The anion exchange membrane (AEMs), its core component, still has problems such as poor alkaline stability, low hydroxide ion conductivity and severe water swelling, which has become an important factor restricting the development of anion exchange membrane fuel cells (AEMFCs).

[0003] Anion exchange membrane is a polyelectrolyte, mainly composed of a polymer skeleton and ion exchange groups connected to it, which can achieve selective permeation of anions. Previous researchers used various topological structures such as side chain type, dense type, and comb type to regulate the self-assembly aggregation behavior of ion exchange groups in the membrane, thereby constructing ion conduction channels. The existence of these ion channels greatly improves the ion transmission rate in the membrane, but there is still a gap with the commercialization goal, mainly because the channel structure is not continuous enough. Summary of the invention

[0004] The present invention aims at the deficiencies in the prior art and provides a copolymer containing a quinine structure and a preparation method and application thereof. The copolymer membrane material containing a quinine structure has good ion conductivity, excellent alkali resistance and mechanical properties, and the preparation method is simple and easy, and has great potential in the application of anion membranes in alkaline fuel cells.

[0005] The technical solution of the present invention to solve the above technical problem is as follows: a copolymer containing a quinine structure, wherein the copolymer containing a quinine structure includes the following general formula I structure:

[0006] Formula I;

[0007] In Formula I, Y1 is selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent;

[0008] Y2 and Y3 are independently selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent, and at least one of Y2 and Y3 is selected from aryl, aralkyl, heteroalkyl, alkyl or perfluoroalkyl, and when one of Y2 and Y3 is absent, the imidazole group to which the existing Y2 or Y3 is connected is neutral;

[0009] Y4 and Y5 are independently selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent, at least one of Y4 and Y5 is selected from aryl, aralkyl, heteroalkyl, alkyl or perfluoroalkyl, and when one of Y4 and Y5 is absent, the imidazole group to which the existing Y4 or Y5 is attached is neutral;

[0010] Ar1, Ar2, Ar3, Ar4, Ar5 are independently selected from substituted or unsubstituted arylene, aralkylene, heteroalkylene, alkylene, perfluoroalkylene, heteroarylene or do not exist; when Ar1, Ar2, Ar3, Ar4, Ar5 contain substituents, they are substituted by 1, 2, 3 or 4 substituents, and the substituents are independently selected from alkyl, aryl, aralkyl, perfluoroalkyl, heteroalkyl, heteroaryl and halogen;

[0011] Ar6, Ar7 are independently selected from substituted or unsubstituted aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl, heteroaryl or hydrogen (H); when it contains substituents, it is substituted by 1, 2, 3, 4 or 5 substituents, and the substituents are independently selected from alkyl, aryl, aralkyl, perfluoroalkyl, heteroalkyl, heteroaryl and halogen;

[0012] R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 are each independently selected from hydrogen, alkyl, aryl, aralkyl, heteroalkyl, heteroaryl, and perfluoroalkyl;

[0013] The heteroatoms in the above heteroalkyl, heteroaryl, heteroalkylene and heteroarylene groups are selected from O, N and S;

[0014] M - fluoride, chloride, bromide, iodide, hydroxide, carbonate, bicarbonate, cyanide, sulfate, phosphate, triflate, and any combination thereof;

[0015] x and y are the percentages of the two structures in the brackets, x is any value between 0.01 and 0.99, y is any value between 0.01 and 0.99, and x+y=1;

[0016] n is an integer between 10 and 1,000,000.

[0017] Furthermore, the copolymer containing quinine structure contains one or more anions M - , wherein the one or more anions M - Counteract one or more positive charges in the polymer.

[0018] Furthermore, the copolymer containing quinine structure includes the following structure:

[0019] .

[0020] Furthermore, Ar1, Ar2, Ar3, Ar4, and Ar5 are independently selected from arylene groups or do not exist; Ar6 and Ar7 are independently selected from aryl groups; and Y1, Y2, Y3, Y4, and Y5 are each independently selected from C1-C5 alkyl groups.

[0021] Furthermore, the copolymer containing quinine structure is selected from any one of the following structures:

[0022] .

[0023] The present invention also discloses a method for preparing a copolymer containing a quinine structure, the method comprising the following steps:

[0024] S1. Synthesis of copolymer:

[0025] Under the protection of inert gas, the monomer combination is dissolved in a solvent, a catalyst and a ligand are added, and then the polymerization is carried out by heat preservation until the reaction system reaches the desired viscosity, and then the polymerization is stopped and the copolymer is obtained through post-treatment;

[0026] Wherein, the monomer combination is: and , X is iodine, bromine or chlorine;

[0027] S2. Functionalization treatment:

[0028] The copolymer obtained in step S1 is dissolved in a solvent, and then a functionalizing agent and a base are added. After the reaction is completed under heating conditions and stirring, the copolymer containing a quinine structure is obtained through post-treatment.

[0029] Furthermore, the monomer combination is selected from any group of the following structures:

[0030] ;

[0031] ;

[0032] ;

[0033] .

[0034] Furthermore, the solvent is any one or a combination of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide;

[0035] The catalyst is any one of trans-1,5,9-cyclododecatriene nickel (0), nickel chloride, and nickel chloride ethylene glycol dimethyl ether complex, and the ligand is 2,2'-bipyridine;

[0036] The functionalizing agent is any one of iodomethane, iodoethane, iodopropane, iodobutane, iodopentane, iodohexane, iodoheptane, iodooctane, iodononane and iododecane;

[0037] The base is any one of sodium bicarbonate, potassium bicarbonate, cesium bicarbonate, sodium carbonate, potassium carbonate, cesium carbonate, calcium carbonate, sodium hydroxide, potassium hydroxide, calcium oxide, and calcium hydroxide, or a combination of several thereof;

[0038] The post-processing process of step S1 and step S2 is: pouring the reaction solution into a precipitant, filtering, washing, and drying to obtain the target product;

[0039] The precipitant is any one or a combination of purified water, industrial hydrochloric acid, phosphoric acid, dilute sulfuric acid, hydrobromic acid, hydrofluoric acid, hydroiodic acid, cyanic acid, and trifluoromethanesulfonic acid.

[0040] Furthermore, in step S1, the dissolution temperature of the monomer combination in the solvent is 20.0°C-60.0°C, the incubation polymerization temperature is 130.0°C-135.0°C, and the incubation polymerization time is 10h-30h;

[0041] In step S2, the heating temperature is 30°C-50°C, the stirring time is 12h-36h, the filtering and washing temperature is 20.0°C-30.0°C; the drying temperature is 90.0°C-120.0°C, and the drying time is more than 24h.

[0042] The invention also discloses an application of a copolymer containing a quinine structure. The copolymer containing a quinine structure is applied to an ion exchange membrane for a fuel cell or for producing hydrogen by hydrolyzing water.

[0043] Among them, the preparation method of the ion exchange membrane of the fuel cell is: the dried copolymer containing quinine structure is dissolved in isopropanol to obtain a uniform solution with a mass fraction of 10%, and the film is coated on a clean glass plate. After drying, the ion exchange membrane is carefully peeled off to obtain the ion exchange membrane, and the ion membrane is immersed in a 1M potassium hydroxide solution, activated for 24h-48h, and then washed with purified water until the aqueous solution is neutral, and dried to obtain the ion exchange membrane material prepared with the quinine structure.

[0044] The beneficial effects of the present invention are:

[0045] The copolymer with quinine structure designed by the present invention makes full use of the structural characteristics of polymer functional groups (such as imidazole and quinine), as well as the "ether-free bond" design and microphase separation structure of the polymer main chain, making it more suitable for alkaline anion exchange membrane. The resonance structure in the functional group of imidazole, and the intra-ring conjugated large π bond and large steric hindrance in the imidazolium salt make the positive charge delocalized and evenly dispersed in the imidazole ring, weakening the aggressiveness of the hydroxide ion; the polymer main chain structure contains aromatic rings such as biphenyl and naphthalene, excluding the ether main chain that is easily decomposed, enhancing the structural rigidity of the membrane material, and can effectively control the water absorption and swelling rate of the membrane material, balance the relationship between the ion exchange capacity (IEC) and the mechanical strength, and enhance the alkali resistance of the membrane material. Secondly, the highly alkaline and stable quininium cation is used to further improve the alkali resistance and ion conductivity.

[0046] The present invention takes strengthening the driving force of self-assembly aggregation of ion exchange groups as the starting point, and through reasonable structural design, regulates the polarity difference between ionized segments and non-ionized segments and the weak interaction between ionized segments to construct efficient ion conduction channels, improve ion conductivity and ensure the alkaline stability of the membrane. The polymer is applied to the ion exchange membrane of alkaline fuel cells and has the beneficial effects of low cost, good mechanical properties, ability to conduct hydroxide ions, high ion conductivity and excellent alkaline resistance.

[0047] In summary, the quinine-structured copolymer designed in the present invention, when used as a membrane material, has high alkali resistance and good mechanical properties, as well as good ion conductivity and appropriate swelling degree, so it has great potential for application in anion membranes of alkaline fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 are the tensile curves of film A, film B, film C, film D, and film E;

[0049] Figure 2 The comparison diagram of the relationship between the swelling degree and temperature of the A film, the B film, the C film, the D film, and the E film;

[0050] Figure 3This is a comparison chart of the stability of membrane A, membrane B, membrane C, membrane D, and membrane E when immersed in 2M sodium hydroxide solution at 80.0°C;

[0051] Figure 4 This is a comparison chart of the relationship between the ion conductivity and temperature of membrane A, membrane B, membrane C, membrane D, and membrane E;

[0052] Figure 5 This is the discharge polarization curve of the hydroxide anion exchange membrane single cell prepared using membrane A. DETAILED DESCRIPTION

[0053] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0055] In the polymer structure of the embodiment, x and y are the percentages of the two structures in the frame, both of which are 50%. The listed polymer structure only shows one possible molecular structure, and does not mean that all molecular chains have this structure, because it is a copolymer and the connection methods within the molecular chain are diverse.

[0056] The coatings and various testing methods mentioned in the specific embodiments are commonly used methods in the industry and are intended to compare the performance of the film materials mentioned in the embodiments.

[0057] 1. Polymer Preparation Example

[0058] Embodiment 1:

[0059] An anion exchange membrane material used in fuel cells, the structural formula of polymer A is:

[0060] ;

[0061] The specific synthetic route of polymer A is:

[0062] ;

[0063] Preparation of A-1: ​​1,4-benzenedicarboxaldehyde (CAS: 623-27-8), 1-(4-chlorophenyl)-2-phenylethane-1,2-dione (CAS: 22711-23-5) and ammonium acetate (CAS: 631-61-8) were weighed in a molar ratio of 1:2.2:12, the solvent was glacial acetic acid, and the amount of the solvent was 10.0 times the weight of 1-(4-chlorophenyl)-2-phenylethane-1,2-dione (CAS: 22711-23-5), and then kept at 110°C for 4 hours. HPLC detection showed that there was no residue of raw materials and the reaction purity was 87.5%. A-1 was obtained after hydrolysis, filtration, boiling and beating, with a yield of 78.5% and an HPLC purity of 98.5%. 1 H NMR (500 MHz, Chloroform- d ): 12.09 (s, 1H), 12.03 (s,1H), 7.88 (s, 4H), 7.56-7.51 (m, 2H), 7.51-7.47 (m, 2H), 7.47-7.37 (m, 9H),7.36 (d, 1H), 7.34-7.24 (m, 4H). LC-MS detection: theoretical molecular weight is 583.53, and the actual detection result molecular weight is 583.0.

[0064] Preparation of A-2: A-1 and potassium hydroxide were weighed at a molar ratio of 1.0:2.2, the solvent was dimethyl sulfoxide, and the amount of solvent was 10.0 times the weight of A-1, and then methyl iodide and A-1 were weighed at a molar ratio of 2.2:1, methyl iodide was added dropwise at 25°C, and then the reaction was kept warm for 1 hour. HPLC detection showed that the reaction purity was 98.0%. A-2 was obtained after hydrolysis, filtration, boiling, and beating, with a yield of 90.5% and an HPLC purity of 99.2%. 1 H NMR (500 MHz, Chloroform- d ): 7.79 (s, 4H), 7.63-7.57 (m,2H), 7.55-7.50 (m, 2H), 7.50-7.32 (m, 13H), 7.32 (d, 1H), 3.83 (s, 6H). LC-MS: The theoretical molecular weight is 611.56, and the actual molecular weight is 611.0.

[0065] Preparation of A-3: 3-quininone hydrochloride (CAS: 1193-65-3) and trifluoromethanesulfonic acid (CAS: 1493-13-6) were weighed at a molar ratio of 1.0:3.0, the substrate solvent was chlorobenzene, the amount of the solvent was 5.0 times the weight of 3-quininone hydrochloride (CAS: 1193-65-3), the temperature was controlled at about 0°C and trifluoromethanesulfonic acid was added dropwise, after the addition was completed, the temperature was raised to 20-30°C and kept for 2 hours, and the reaction purity was 83.5% after GC detection. A-3 was obtained through hydrolysis, alkalization, extraction, water washing, solvent removal, and recrystallization, with a yield of 70.1% and a GC purity of 95.5%. 1 H NMR (500 MHz, Chloroform- d ): 7.32–7.26 (m, 4H), 7.21–7.16 (m, 4H),3.76 (s, 2H), 2.85 (t, 4H), 2.36 (d, 1H), 1.87–1.79 (m, 4H). GC-MS: The theoretical molecular weight is 332.3, and the actual molecular weight is 332.0.

[0066] Preparation of A-4: A-2 and A-3 were weighed at a molar ratio of 1.0:1.0, and then A-2 and N,N-dimethylformamide were weighed at a weight ratio of 1.0:30.0. A-2 and A-3 were dissolved in N,N-dimethylformamide, and nickel chloride and 2,2'bipyridine were added at low temperature and under the protection of inert gas. The molar ratio of A-2 to catalyst and ligand was 1.0:4.0:4.0. Then the reaction was kept at 130°C for 30 hours. When the system was a viscous liquid, the heat preservation reaction was stopped. The reaction solution was controlled to be below 30.0°C, slowly hydrolyzed into hydrochloric acid for precipitation, and then filtered, washed, and dried to obtain A-4.

[0067] Preparation of polymer A: A-4 was dissolved in 40.0 times of N,N-dimethylformamide, and A-4, 1-iodobutane and potassium hydroxide were weighed in a molar ratio of 1.0:4.0:4.0. The mixture was stirred at 30°C for 10 hours, and then the reaction solution was hydrolyzed into hydrochloric acid for precipitation. After filtering, washing and drying, polymer A was obtained.

[0068] Embodiment 2:

[0069] An anion exchange membrane material used in fuel cells, the structural formula of polymer B is:

[0070] ;

[0071] The specific synthetic route of polymer B is:

[0072] ;

[0073] The preparation of polymer B is different from that of polymer A in that 1,4-benzenedicarboxaldehyde (CAS: 623-27-8) in preparation A-1 is replaced by [1,1'-biphenyl]-4,4'-dicarboxaldehyde (CAS: 66-98-8), chlorobenzene in preparation A-3 is replaced by dichloroethane, and 3-quinidone hydrochloride (CAS: 1193-65-3) and 4-chlorobiphenyl (CAS: 2051-62-9) are added in a molar ratio of 1.0:1.0, and then polymer B is prepared according to the process for preparing polymer A.

[0074] Embodiment 3:

[0075] An anion exchange membrane material used in a fuel cell, the structural formula of the polymer C is:

[0076] ;

[0077] The specific synthetic route of polymer C is:

[0078] ;

[0079] The difference between the preparation of polymer C and the preparation of polymer A is that 1,4-benzenedicarbaldehyde (CAS: 623-27-8) in the preparation of A-1 is replaced with 1,5-naphthalenedicarbaldehyde (CAS: 7141-15-3), and then polymer C can be prepared according to the process for preparing polymer A.

[0080] Embodiment 4:

[0081] An anion exchange membrane material used in fuel cells, the structural formula of polymer D is:

[0082]

[0083] The specific synthetic route of polymer D is:

[0084] ;

[0085] The preparation of polymer D is different from that of polymer A in that 1,4-benzenedicarbaldehyde (CAS: 623-27-8) in preparation A-1 is replaced with 9,10-dihydro-9,10-anthracenedicarboxaldehyde (CAS: 71440-45-4), and then polymer D is prepared according to the process for preparing polymer A.

[0086] Comparative Example

[0087] Fuel cell anion exchange membrane polymer E structure:

[0088] ;

[0089] According to the information disclosed in Chinese patent CN116693785B, the F1h alkaline anion exchange membrane in Example 1 mentioned in the patent was prepared.

[0090] 2. Polymer Application: Coating and Related Testing

[0091] Coating: The polymers A, B, C, D and E synthesized in Example 1, Example 2, Example 3, Example 4 and the comparative example are respectively prepared into a casting liquid with a mass fraction of 10% with isopropanol. Then, the casting liquid is respectively coated on a clean glass plate with a scraper, and the coating thickness is 40-50 microns. Then, the solvent is evaporated and carefully peeled off to obtain the corresponding ion exchange membrane material. Then, the ion exchange membrane is functionalized and infiltrated into a 1M potassium hydroxide solution respectively. After soaking for 48 hours, the membrane is taken out and washed with deionized water until the aqueous solution is neutral. Then, it is dried at 100°C for 48 hours to obtain the corresponding hydroxide-type alkaline fuel cell anion exchange membranes of polymer A, polymer B, polymer C, polymer D and polymer E: A membrane, B membrane, C membrane, D membrane and E membrane. Then, the A membrane, B membrane, C membrane, D membrane and E membrane are subjected to relevant tests and the single cell performance test of the corresponding membrane:

[0092] 1. Mechanical properties: The test was carried out in accordance with GB T 20042.3. The tensile test was carried out under environmental conditions (23.0°C, 20% relative humidity). The test was carried out on a universal tensile testing machine (SANS CMT8102) at a tensile speed of 1 cm / min.

[0093] Figure 1 is the tensile curve of the membrane material. Due to the difference in rigidity of the membrane material structure, the tensile strain of the membrane material is different. In general, the strain values ​​of membrane A, membrane B, membrane C, membrane D, and membrane E at break are between 20% and 25%, which is not much different and can meet the use requirements of alkaline fuel cell membranes.

[0094] 2. Solubility test: Add 1.0 g of polymer into 30.0 g of solvent, heat at 80.0°C and stir to aid dissolution, and observe its dissolution.

[0095] Intrinsic viscosity test: The polymers were dissolved in dimethyl sulfoxide to prepare a clear solution with a concentration of 1.0%, and measured with an Ubbelohde viscometer at 23.0°C. The specific test results are shown in Table 1 below.

[0096] Table 1 Viscosity and solubility of membrane materials

[0097]

[0098] Note: ++ means soluble at room temperature, +- means swellable at room temperature, and -- means insoluble even when heated.

[0099] Table 1 shows the viscosity and solubility of film A, film B, film C, film D, and film E. Based on the solubility of each film and the ease of solvent removal, isopropyl alcohol was selected as the film coating solvent. The viscosity of each film is moderate, meeting the needs of film coating.

[0100] 2. Water absorption and swelling ratio: Use a knife die to cut several 10mm*50mm small sample strips, vacuum dry them at 80℃ for 24h, quickly measure their dry weight, and then soak them in a constant temperature water bath at 40℃ and 80℃ for 24h, wipe the surface of the membrane with filter paper, and weigh its water absorption weight. Then place the membrane on a glass plate, measure the length of the membrane with a vernier caliper, and calculate the water absorption (water up) and volume swelling ratio (swelling ratio) of the membrane. The calculation formulas for water absorption and swelling ratio are as follows: Water absorption = m a -m b / m a ×100%, swelling rate = l a -l b / l b ×100%, where m a , l a m are the mass and length of the membrane after immersion in a water bath at a specific temperature for 24 hours; m b , l b The specific measurement results are shown in Table 2 below.

[0101] Table 2 Water absorption of membrane materials

[0102]

[0103] Figure 2 Table 2 is the corresponding relationship between the swelling degree and temperature of membrane A, membrane B, membrane C, membrane D, and membrane E, and Table 3 is the water absorption rate of the membrane material. The water absorption rate of the alkaline anion exchange membrane directly determines the ion conductivity of the membrane material, but the membrane material will swell after absorbing water. Too high a swelling rate will cause the membrane material to face problems such as catalyst shedding, affecting the service life of the membrane electrode. Based on parameters such as water absorption rate and swelling degree, membrane A, membrane B, membrane C, membrane D, and membrane E can meet the basic use requirements of alkaline fuel cell membranes.

[0104] 3. Alkali stability: Soak the membrane material in 2M potassium hydroxide solution at 80.0℃, take out a sample every 120 hours, wash the membrane material with deionized water until the aqueous solution is neutral, and then test the ionic conductivity of the membrane material. The alkaline stability of the membrane is determined by the retention rate of the ionic conductivity.

[0105] Figure 3The stability of the membrane material immersed in a 2M potassium hydroxide solution at 80.0°C. From the data, it can be analyzed that the conductivity of membrane A, membrane B, membrane C, and membrane D is kept in alkaline solution for 840 hours and remains above 90%, and the conductivity of membrane E is kept in alkaline solution for 840 hours and remains above 84%. After 720 hours, the degradation rate of membrane E is significantly faster than that of the other membranes. The alkali resistance of membrane materials is affected by factors such as the stability of the polymer main chain structure and the water absorption rate. The membrane electrode is in a strong alkaline environment during operation. The alkali resistance of membrane materials is an important factor to consider regarding the life of alkaline fuel cells. Therefore, membrane materials are preferably membrane A, membrane B, membrane C, and membrane D, which are used as alkaline fuel cell membranes.

[0106] 4. Ionic conductivity: The ionic conductivity was tested by the AC impedance method, and the in-plane conductivity of the ion membrane was measured using an electrochemical workstation (CHI660C, Shanghai Chenhua Instrument Co., Ltd., Shanghai). The test frequency was 1 to 10 5 Hz. During the test, the ion membrane is clamped in a tetrafluoroethylene mold with two platinum electrodes, and the AC impedance test is performed in constant current mode. Ionic conductivity = distance between two electrodes / cross-sectional area of ​​the membrane in the electric field / membrane resistance.

[0107] Figure 4 is the relationship between the ion conductivity of the membrane material and temperature. The ion conductivity is related to both water absorption and temperature. As the temperature rises, the water absorption increases, the membrane material partially swells, and the ion conductivity increases. From the data, the conductivity of membrane A, membrane B, membrane C, membrane D, and membrane E can meet the basic use requirements of alkaline fuel cell membranes, but the conductivity of membrane E is relatively low. Therefore, membrane materials are preferably membrane A, membrane B, membrane C, and membrane D for use as alkaline fuel cell membranes.

[0108] 5. In order to evaluate the practical application effect of the highly stable ion exchange membrane of the present invention, membrane A with better comprehensive parameters was selected to assemble the membrane electrode first, and then made into a single cell for performance testing.

[0109] Preparation of membrane electrode: First, the membrane electrode assembly is prepared by CCS method, that is, the catalyst ink is sprayed on carbon paper, and then the carbon paper and membrane material are contacted by hot pressing. The cathode and anode catalysts are platinum carbon and platinum ruthenium carbon respectively, and the loading of metal platinum is 1mg / cm 2 The mass ratio of catalyst to ion polymer is 4.0:1.0, then the catalyst, isopropanol, and polymer dimethyl sulfoxide solution (5.0% mass fraction) are mixed and dispersed evenly by ultrasound. The mixed solution is evenly sprayed on carbon paper to make a gas diffusion electrode. The membrane is sandwiched between the two electrodes, and the electrodes and the membrane are pressed into a membrane electrode assembly by external force at room temperature.

[0110] Single cell assembly and performance test: The sealing gasket, graphite flow field, gold-plated current collector, insulating pad and heating end plate are assembled on both sides of the membrane electrode to obtain a single cell. The effective area of ​​the electrode is 1cm 2 The performance was tested using a fuel cell workstation (Arbin Instrument, College station, TX) under the following conditions: at 60.0°C, a hydrogen flow rate of 500 mL / min, an oxygen flow rate of 150 mL / min, and a relative humidity of 100%.

[0111] Figure 5 This is the discharge polarization curve of a single hydrogen-oxygen anion exchange membrane cell. From the test data, we can see that the open circuit voltage of the single cell is 1.05V and the maximum power density of the single cell is 525mW / cm 2 When the maximum power density is reached, the corresponding current density is 700.0mA / cm 2 , the voltage is 0.75 V. The single cell maintains good operating stability within the observed time interval of the test, which fully demonstrates that the high-performance ion exchange membrane obtained by the present invention can be used as a membrane material for fuel cells.

[0112] It can be seen from the above relevant test data that membrane A, membrane B, membrane C and membrane D can all meet the use requirements of alkaline fuel cell ion exchange membranes. The membrane electrode assembly prepared with membrane A has also been proved by single cell performance test that this copolymer material can be used as a membrane electrode material for fuel cells. Compared with the publicly reported E membrane (prepared according to patent number: CN116693785B), the comprehensive performance of membrane A, membrane B, membrane C and membrane D is more outstanding. When the copolymer described in the present invention is used for membrane electrodes, it not only has good ion conductivity and moderate swelling rate, but also has excellent alkali resistance. Therefore, this copolymer is used in membrane electrodes and has great potential in the application of alkaline fuel cells.

[0113] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0114] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A copolymer containing a quinine structure, characterized in that: The copolymer containing quinine structure is selected from any one of the following structures: ; n is an integer between 10 and 1,000,000.

2. A method for preparing a copolymer containing a quinine structure according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Synthesis of copolymer: Under the protection of inert gas, the monomer combination is dissolved in a solvent, a catalyst and a ligand are added, and then the polymerization is carried out by heat preservation until the reaction system reaches the desired viscosity, and then the polymerization is stopped and the copolymer is obtained through post-treatment; Wherein, the monomer combination is selected from any group of the following structures: ; ; ; ; S2. Functionalization treatment: The copolymer obtained in step S1 is dissolved in a solvent, and then a functionalizing agent and a base are added. After the reaction is completed under heating conditions and stirring, the copolymer containing a quinine structure is obtained through post-treatment.

3. The method for preparing a copolymer containing a quinine structure according to claim 2, characterized in that: The solvent is any one or a combination of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide; The catalyst is any one of trans-1,5,9-cyclododecatriene nickel (0), nickel chloride, and nickel chloride ethylene glycol dimethyl ether complex, and the ligand is 2,2'-bipyridine; The functionalizing agent is any one of iodomethane, iodoethane, iodopropane, iodobutane, iodopentane, iodohexane, iodoheptane, iodooctane, iodononane and iododecane; The base is any one of sodium bicarbonate, potassium bicarbonate, cesium bicarbonate, sodium carbonate, potassium carbonate, cesium carbonate, calcium carbonate, sodium hydroxide, potassium hydroxide, calcium oxide, and calcium hydroxide, or a combination of several thereof; The post-processing process of step S1 and step S2 is: pouring the reaction solution into a precipitant, filtering, washing, and drying to obtain the target product; The precipitant is any one or a combination of purified water, industrial hydrochloric acid, phosphoric acid, dilute sulfuric acid, hydrobromic acid, hydrofluoric acid, hydroiodic acid, cyanic acid, and trifluoromethanesulfonic acid.

4. The method for preparing a copolymer containing a quinine structure according to claim 3, characterized in that: In step S1, the dissolution temperature of the monomer combination in the solvent is 20.0°C-60.0°C, the insulation polymerization reaction temperature is 130.0°C-135.0°C, and the insulation polymerization reaction time is 10h-30h; In step S2, the heating temperature is 30°C-50°C, the stirring time is 12h-36h, the filtering and washing temperature is 20.0°C-30.0°C; the drying temperature is 90.0°C-120.0°C, and the drying time is more than 24h.

5. An application of a copolymer containing a quinine structure according to claim 1, characterized in that: The copolymer containing quinine structure is applied to ion exchange membranes for fuel cells or water splitting to produce hydrogen.

Citation Information

Patent Citations

  • A type of nitrogen-containing heterocyclic polymer, a type of polymer film and its application

    CN116693785B

  • Tetraphenol monomer, intrinsic microporous polymer, iodomethanated intrinsic microporous polymer, and preparation method and application of tetraphenol monomer, intrinsic microporous polymer and iodomethanated intrinsic microporous polymer

    CN118598796A